2008
DOI: 10.1128/cvi.00416-07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Antibodies on Efficacy of Porcine Circovirus Type 2 (PCV2) Vaccination To Protect Pigs from Experimental Infection with PCV2

Abstract: Due to the ubiquitous nature of porcine circovirus type 2 (PCV2) in the pig population and the increasing use of PCV2 vaccines in breeding herds, the majority of dams have been exposed to field PCV2 or PCV2 vaccines, resulting in piglets with varied levels of passively acquired PCV2 maternal antibodies. The objective of the current research was to investigate the influence of passively acquired anti-PCV2 antibodies on PCV2 vaccine efficacy. Sixty 26-day-old pigs were divided into four groups: vaccinated pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 19 publications
3
63
0
1
Order By: Relevance
“…Several research groups have studied the efficacy of commercial PCV2 vaccines in pigs singularly infected with PCV2 (30,31) or in pigs concurrently infected with multiple pathogens (33,42). In all previous studies, vaccination was done according to the manufacturer's label instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have studied the efficacy of commercial PCV2 vaccines in pigs singularly infected with PCV2 (30,31) or in pigs concurrently infected with multiple pathogens (33,42). In all previous studies, vaccination was done according to the manufacturer's label instructions.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that PCV2 viremia in the blood is not reflected in the levels of PCV2 antibodies in the blood. It has been reported that a reduced PCV2 load in the serum is unrelated to the serum antibody response to the PCV2 vaccine (16,18). Boars in the vaccinated challenged and nonvaccinated challenged group had detectable serum levels of anti-PCV2 IgG, indicating successful vaccination and/or challenge.…”
Section: Discussionmentioning
confidence: 92%
“…PCV2 vaccines decrease the PCV2 load in the serum and reduce PCV2 shedding in nasal and fecal samples in conventional pigs (5). Commercial vaccines were shown to be able to control two of the multiple disease entities, known as PMWS and PRDC (2,4,5,16,18). To our knowledge, this is the first application of a PCV2 vaccine in boars to determine its effect on PCV2 shedding in the semen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays are organized by submitting laboratory and type of assay; indirect fluorescent antibody tests (IFA), in-house enzyme-linked immunosorbent assays (ELISA), and commercially available (Serelisa g [S] or Ingezim f [I]) ELISAs. tal studies, 14 there were likely consistently high levels of antibodies present at this point, which enhanced uniformity in test results in comparison with samples taken from animals shortly after PCV-2 infection as evident in the kappa values (poor to almost perfect) obtained on trial day 14.…”
Section: Discussionmentioning
confidence: 99%